Gender-related effects on substrate utilization and metabolic adaptation in hairless spontaneously hypertensive rat - Trnovská, J; Šilhavý, J; Zídek, V; Šimáková, M; Mlejnek, P; Landa, V; Eigner, S; Eigner Henke, K; Škop, V; Oliyarnyk, O; Kazdová, L; Mráček, T; et al. (Physiological research, 2015)
Cold exposure of rats leads to ameliorated glucose and triglyceride utilization with females displaying better adaptation to a cold environment. In the current study, we used hairless rats as a model of increased thermogenesis and analyzed gender-related effects on parameters of lipid and glucose metabolism in the spontaneously hypertensive (SHR) rats. Specifically, we compared hairless coisogenic SHR-Dsg4 males and females harboring mutant Dsg4 (desmoglein 4) gene versus their SHR wild type controls. Two way ANOVA showed significant Dsg4 genotype (hairless or wild type) x gender interaction effects on palmitate oxidation in brown adipose tissue (BAT), glucose incorporation into BAT determined by microPET, and glucose oxidation in skeletal muscles. In addition, we observed significant interaction effects on sensitivity of muscle tissue to insulin action when Dsg4 genotype affected these metabolic traits in males, but had little or no effects in females. Both wild type and hairless females and hairless males showed increased glucose incorporation and palmitate oxidation in BAT and higher tissue insulin sensitivity when compared to wild type males. These findings provide evidence for gender-related differences in metabolic adaptation required for increased thermogenesis. They are consistent with the hypothesis that increased glucose and palmitate utilization in BAT and muscle is associated with higher sensitivity of adipose and muscle tissues to insulin action.
Keywords: potkani bezsrstí; Sex Factors; přijímání potravy; Eating; regulace genové exprese; Hypertension; Adaptation, Physiological; desmogleiny; oxidace-redukce; termogeneze; mutace; Female; nízká teplota; Phenotype; Genotype; zvířata; glukosa; Cold Temperature; kyselina palmitová; Rats, Hairless; sexuální faktory; Adiposity; hnědá tuková tkáň; kosterní svaly; Energy Metabolism; Palmitic Acid; ženské pohlaví; energetický metabolismus; Gene Expression Regulation; Male; potkani inbrední SHR; hypertenze; Desmogleins; fenotyp; Glucose; Insulin; Muscle, Skeletal; fyziologická adaptace; Oxidation-Reduction; genotyp; Animals; Thermogenesis; Mutation; mužské pohlaví; Adipose Tissue, Brown; Disease Models, Animal; adipozita; Rats, Inbred SHR; inzulin; modely nemocí na zvířatech